The Effect of Interest in Sports on the Learning Outcomes of Fifth Grade Students in Physical Education - Muhammad Tahir; Zaini Hasan; Orbit Irwansyah (STMIK Indonesia Banda Aceh, 2026)
This study aims to examine the effect of interest in sports on the learning outcomes of fifth-grade students in physical education at SD Negeri Kampung Bakti in the 2025 academic year. This study uses a quantitative approach methodology. A quantitative research approach can be defined as a research method used to study a specific population or sample, with quantitative/statistical data analysis aimed at testing predetermined hypotheses. In this study, the sample was selected using the Purposive Sampling technique determined by the researcher with a total of 27 students. Data To collect data for this study, documentation, tests, and questionnaires were used. The results of this study are as follows: In the discussion of the sports interests of fifth-grade students at SD Negeri Kampung Bakti in the 2025 academic year, 19% were in the low category, 59% were in the medium category, and 22% were in the high category. Meanwhile, in the discussion of fifth-grade learning outcomes in the subject of Physical Education subject for fifth-grade students at SD Negeri Kampung Bakti in the 2025 academic year, the results are 11% in the low category, 78% in the moderate category, and 11% in the high category. Conclusion In this study, the analysis of the data found a significant effect between interest in sports and student learning outcomes in the subject of Physical Education, amounting to 19.9%. Thus, Ha is accepted and states that there is an effect of interest in sports on student learning outcomes.